2008
DOI: 10.1177/112067210801800111
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Endophthalmitis following Trabeculectomy in a Chinese Population

Abstract: Physicians should weigh the benefits against the risks of mitomycin C application in performing trabeculectomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Intraoperative 5-FC or MMC are recognised as important risk factors for bleb-related infection 22 51 75. A Cochrane review concluded that intraoperative MMC reduced the risk of surgical failure, but complications such as infection could not be evaluated due to inadequate power 76.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative 5-FC or MMC are recognised as important risk factors for bleb-related infection 22 51 75. A Cochrane review concluded that intraoperative MMC reduced the risk of surgical failure, but complications such as infection could not be evaluated due to inadequate power 76.…”
Section: Discussionmentioning
confidence: 99%
“…At the Singapore National Eye Centre, all trabeculectomies are performed with adjunctive anti-fibrotic agents, MMC being the preferred choice. Rates of BRE after using MMC have been reported at 1.1%–3.2% 2,4,15,16. While Mochizuki et al’s study demonstrated similar BRI rates of 1.3% and 1.1% with 5-FU and MMC, respectively 4.…”
Section: Introductionmentioning
confidence: 94%
“…Kuang et al . [9] in a retrospective study reported only one case, out of 988 trabeculectomies, with early post-operative endophthalmitis due to Morganella morganii . Host flora is usually responsible for early cases of endophthalmitis and Staphylococcus epidermitis is the most common organism.…”
Section: Discussionmentioning
confidence: 99%